Determination of Abnormal Returns from the Point of View of Environmental Performance In Mining Companies - Yunita, Nur Afni; juliani, Juliani; Naz'aina, Naz'aina; yusra, Muhammad (Department of Accounting, Faculty of Economics & Business, 2024)
This research aims to examine the influence of environmental, social and governance on abnormal returns. The sample in this research are mining companies that disclosed ESG disclosure scores in 2020-2022. The sampling technique used was purposive sampling to obtain 45 companies that disclosed ESG disclosure scores for 3 consecutive years from 2020-2022. Testing in this research uses descriptive statistics and hypothesis testing. The results of this study show that environmentalism has no effect on abnormal returns. However, social and governance have a positive effect on abnormal returns